Bioaugmentation process of secondary effluents for reduction of pathogens, heavy metals and antibiotics - Adel, Ali Saeed Abduh Algheethi; Radin Mohamed, Radin Maya Saphira; AN, Efaq; I, Norli; Abdullah, Abd Halid; HK, Amir; MO, Ab Kadir (IWA Publishing, 2016)
The study probed into reducing faecal indicators and pathogenic bacteria, heavy metals and β-lactam antibiotics, from four types of secondary effluents by bioaugmentation process, which was conducted with Bacillus subtilis strain at 45 'C. As a result, faecal indicators and pathogenic bacteria were reduced due to the effect of thermal treatment process (45 'C), while the removal of heavy metals and β-lactam antibiotics was performed through the functions of bioaccumulation and biodegradation processes of B. subtilis. Faecal coliform met the guidelines outlined by WHO and U. S. EPA standards after 4 and 16 days, respectively. Salmonella spp. and Staphylococcus aureus were reduced to below the detection limits without renewed growth in the final effluents determined by using a culture-based method. Furthermore, 13.5% and 56.1% of cephalexin had been removed, respectively, from secondary effluents containing 1 g of cephalexin L1 (secondary effluent 3), as well as 1 g of cephalexin L1 and 10 mg of Ni2 L1 (secondary effluent 4) after 16 days. The treatment process, eventually, successfully removed 96.6% and 66.3% of Ni2 ions from the secondary effluents containing 10 mg of Ni2 L1 (secondary effluent 2) and E4, respectively. The bioaugmentation process improved the quality of secondary effluents.